Design and Fabrication of a Hydraulic Transmission Jack for Heavy-Duty Truck Maintenance - Van Anh, Nguyen; Mai, Hoang Thi (Yayasan Kawanad, 2025)
This study presents the design, fabrication, and testing of a hydraulic transmission jack specifically tailored for lifting and handling truck transmissions in automotive repair facilities. The device utilizes a foot-operated hydraulic system to provide efficient and safe lifting capabilities, addressing the ergonomic and safety challenges associated with manual handling of heavy transmissions during removal and installation procedures. Through systematic design calculations, material selection, structural analysis, and prototype assembly, the jack achieves a lifting capacity of 2000 kg with a height adjustment range of 190–810 mm, suitable for medium to heavy-duty truck applications. Comprehensive performance testing demonstrated reliable operation under maximum load conditions, with no structural failure, hydraulic leakage, or stability issues observed during extended hold tests and offset load scenarios up to 1500 kg. The prototype was fabricated at approximately 300, representing 35–50% cost savings compared to commercially available models while maintaining comparable performance characteristics. The foot-pedal hydraulic operation enables hands-free lifting with controlled positioning, significantly reducing physical strain on mechanics and potentially decreasing workplace injuries. Stability tests confirmed adequate resistance to tipping under asymmetric loading conditions, while the 45 kg overall weight and caster-mounted base provide acceptable portability for workshop environments. This innovation contributes to advancing mechanical engineering applications in vehicle maintenance by demonstrating that effective ergonomic solutions can be achieved through practical design approaches using readily available materials and components, making specialized lifting equipment more accessible to small-scale repair facilities, particularly in developing economies where capital investment constraints limit access to commercial equipment.